Evaluating the quality of services provided in women’s toilets around Al-Masjid Al-Haram - Ashour, Khdijah Youseef (Journal of Economic, Administrative and Legal Sciences, 2022)
Purpose- This study aims to assess the quality of services provided in women's toilets around Al-Masjid Al-Haram, by identifying the services provided in women's toilets around Al-Masjid Al-Haram, and identifying the most important health requirements available, and then measuring the level of quality of services provided there.Design / Methodology / Approach- To achieve the objectives of this study, the descriptive analytical approach was applied, due to its relevance to the nature of the study problem and its ability to achieve its objectives, in addition to applying a set of appropriate statistical methods. The study tool (the questionnaire) according to the model, and some of its phrases were reformulated in a way that suits the population and sample of the study. In addition to the researcher's use of the observation form to reflect the actual reality of the toilets and evaluate the quality of the service provided from the researcher's point of view, where (4) toilets were randomly selected from different women's toilets on the western and southern sides of the courtyards of Al-Masjid Al-Haram.Findings- The study reached many results, the most important of which are: that the women’s toilets distributed around Al-Masjid Al-Haram (which are available in them) apply the five dimensions of service quality, which are reliability, tangibility, empathy, safety, and response. from the point of view of visitors and users of women’s courses around Al-Masjid Al-Haram, taking into account Consider that this availability (application) varies among the five dimensions. The evaluation of visitors and users of the same dimensions was similar with respect to all dimensions. The study did not show any differences in the evaluation of visitors and users of quality dimensions due to any of the demographic variables. The researcher recommends many issues related to quality dimensions indicators, the most important of which are: the commitment of those in charge of serving the pilgrims to provide and provide health requirements for toilets distributed around Al-Masjid Al-Haram, and the development of smart toilets that comply with international quality standards for toilets, such as those established at international airports. The presence of a digital system linked to the quality of the sanitary ware used, the development of sanitary ware, and the allocation of places to store visitors' luggage.
Keywords: the Grand Mosque; Hajj; Umrah; spending on education; digital transformation